Analysis of Management Policy and Management Performance Green Accounting with Green Economy and Csrd as An Intervening Variable in Pharmacy Companies Listed on the Indonesian Stock Exchange - Fara Brygita Ramadhani; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze management policies and management performance on green accounting with green economy and corporate social responsibility disclosure as intervening variables. The research method uses a descriptive quantitative research design. The research data utilizes financial reports of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. The population used in this study is pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. Sample selection is done using purposive sampling method, resulting in a sample of 9 pharmaceutical sub-sector companies out of a total population of 11. The statistical data processing tool in this study uses SmartPLS software with outer model analysis consisting of convergent validity, construct reliability and validity, and discriminant validity. The inner model analysis in this study is used to test the hypotheses that have been made. The results obtained in this study indicate that the hypothesis testing directly shows only the green economy significantly influences CSRD, while management policies do not have a direct effect on green accounting, green economy, CSRD, or management performance. Additionally, management performance does not affect the green economy, green accounting, or CSRD, and the green economy does not affect green accounting or CSRD. Indirect hypothesis testing results show that the green economy cannot intervene in management policies or management performance on green accounting, and CSRD cannot intervene in management policies or management performance on green accounting.